An Avoidance of Online Gaming Through Islamic Literature (Case Study: Senior High School Student) - Mahfuzh Hasby Asy Syukri; Wisnu Uriawan; M Hasbi Hasbullah; Fazli Mawla Ghifari; Faza Mohamad Farsyafat (Progressive Journal of Educational Science, 2025)
This study aims to understand the role of Islamic education in reducing online gaming addiction among high school students. Using a case study approach, data were collected through interviews, observations, and document analysis to explore how Islamic literature can serve as an effective medium to raise awareness about the dangers of online gaming addiction. The findings reveal that Islamic values, such as time manage- ment, ethics, and self-control, significantly influence students’ behavior regarding technology use. Religious activities, such as congregational prayers and Quranic study groups, provide a supportive social environment that helps divert attention from online gaming. However, challenges such as peer pressure and the lack of digital literacy among parents hinder the effective implementation of these Islamic values. The study suggests a holistic approach that integrates Islamic education with practical strategies to manage technology use wisely. This approach not only addresses online gaming addiction but also fosters the development of a generation that is creative, productive, and deeply rooted in Islamic principles.